Perceptions of 9th grade elementary school students about the Mangrove flora (Research, Society and Development, 2022)
The Mangrove has several important and economic natural purposes, in addition to being a place of various reproductions of marine species and birds, as well as found in the neighborhood of Sabiaguaba, located on the east coast of the city of Fortaleza-CE. Therefore, this work was developed with the objective of verifying the perceptions of the students of the 9th year of Elementary School of the public school of Sabiaguaba about the flora of the Mangrove, as they live with this ecosystem, in addition to the contribution of popular knowledge of the local community. For this, a semi-structured field with multiple discussion questions was elaborated, which was applied with 64 students of the 9th year of Elementary School at Escola Municipal Professor Manuel Eduardo Pinheiros. Most of the participants were male, prevailing the age group of 14 years and most residing in the neighborhood of Sabiaguaba. Most students never visited the Sabiaguaba Mangrove, in addition, they did not answer satisfactorily what the Mangrove was, but declared they were interested in learning more about its flora. Regarding the importance of this ecosystem and whether its plants were different from the others, most students responded unsatisfactorily. The vast majority of students were unable to list typical Mangrove plants, they do not use these in their daily lives and do not recognize them as images of the typical Mangrove flora. Therefore, it is concluded that despite the students being inserted in this ecosystem, their knowledge about Mangroves is limited, probably due to the absence of field classes.